2011
DOI: 10.1103/physrevb.84.064105
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of elastic moduli of polycrystalline β plutonium

Abstract: The elastic moduli of pure polycrystalline beta plutonium were measured over its full range of existence (417 K to 491 K) using resonant ultrasound spectroscopy. The Debye temperature (138 K), Poisson's ratio (0.28), Grüneisen parameter (2.3), and the zerotemperature atomic volume (21.2 Å 3 ) were computed from the measurements. Both bulk and shear moduli decrease smoothly on warming with expected discontinuities at the phase boundaries. The shear modulus is surprisingly nearly the same for beta and gamma Pu. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 81 publications
4
30
0
Order By: Relevance
“…According to our data at the point of phase transition from a-to b-phase of Np a quite dramatic change of the bulk modulus occurs: b-Np exhibits lower values of the bulk modulus and its weaker temperature depende nce. It is worth noting that the similar changes are observed at the phase transition from a-to b-phase of plutonium [5]. However, in order to verify the results of our calculations , a big amount of experimental data on the bulk modulus of neptunium is required, whereas at the present moment this data is extremely sparse.…”
Section: The Results and Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…According to our data at the point of phase transition from a-to b-phase of Np a quite dramatic change of the bulk modulus occurs: b-Np exhibits lower values of the bulk modulus and its weaker temperature depende nce. It is worth noting that the similar changes are observed at the phase transition from a-to b-phase of plutonium [5]. However, in order to verify the results of our calculations , a big amount of experimental data on the bulk modulus of neptunium is required, whereas at the present moment this data is extremely sparse.…”
Section: The Results and Discussionsupporting
confidence: 70%
“…Thus, for palladium and platinum in the entire range of their existence C does not exceed 3.1 [12]. Comparing to plutonium [5] we can point that neptunium possess the values of the Gruneise n parameter, which are typical for d-Pu (C = 3.8 at T = 480 K) but higher than in the case of b-Pu (C = 2.3 at T = 450 K) and c-Pu (C = 1.9 at T = 550 K). This confirms the presence of strong phonon anharmonicity of neptunium.…”
Section: The Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This model could be made to fit δ-Pu's volume versus temperature dependence as measured by elastic neutron scattering for the range of Ga concentrations typically used to stabilize the δ-phase (4). However, measurements of the elastic moduli of polycrystalline Pu-Ga alloys by Suzuki et al (5) showed that the bulk modulus softened substantially on warming in temperature regions where the atomic volume remained fixed. In an attempt to include elastic softening as temperature increased and volume decreased, Lawson et al (1) made the unusual conjecture that the higher energy state with smaller volume, required to get the thermal expansion correct, must make no contribution to the bulk modulus.…”
mentioning
confidence: 99%